An Overview of Learning Evaluation Practices in the 2013 Curriculum and Independent Curriculum at Integrated Islamic Kindergarten - Yunanda, Rizkia; Zuhaira M, Shafa; Raihana, Syifa; Yolla, Yelniva; Indah Zaskia, Tina; Amelia, Lina; Al Salmi, Maryam (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
Learning evaluation is an essential component in the educational process which functions to assess student competency achievement. This research aims to describe the implementation of learning evaluation at Baitusshalihin Integrated Islamic Kindergarten, with a focus on two curricula, namely the 2013 Curriculum and the Merdeka Curriculum. By applying a qualitative approach, data was obtained through interviews with educators and observations of the evaluation process carried out. The research results indicate that the implementation of assessment in the 2013 Curriculum emphasizes assessment based on standardized learning outcomes using authentic methods. In contrast, the Merdeka Curriculum offers greater flexibility in evaluation, allowing adjustments to the needs and potential of each student. Baitusshalihin IT Kindergarten uses a project-based assessment method.